Families Who Return to the Child Welfare System after a Previous Termination of Parental Rights: Few in Number, High in Court Utilization. (25th September 2020) - Davidson, Ryan D.; Irgens, Megan S.; Beck, Connie J.
Abstract : Anecdotally, judges, court staff and behavioral health providers working in the child welfare system indicate that families commonly return to the system after a termination of parental rights. The current study is the first to empirically investigate these families who return to the system with new children. Results show that although only a small proportion of families returned after a previous termination of parental rights, these families often returned multiple times with new children. Future research should attempt to replicate these results in other jurisdictions and focus on risk and protective factors to better understand the needs of these parents and children, and determine how to better support them within the child welfare system. Abstract : Key Points for the Family and Juvenile Court Community: Less than 10% of the families who returned to the child welfare system within one calendar year in 2007 returned following a termination of parental rights. Families returned to the system, on average, less than a year after the previous case was closed. Children in the new cases following their parents' previous termination of parental rights tended to be younger than children in the original cases. Parental substance abuse and failure‐to‐protect were the most commonly reported reasons for removal when families returned after a termination of parental rights. Many families experienced more than one case ending in a termination of parental rights. Families who returned to the child welfare system after a termination of parental rights had an average of five separate cases/dependency petitions including both prior to and following the case in this study ending in a termination of parental rights. Additional research is needed to aid in identification of risk factors for families returning so that new skills and additional support may be provided for families at risk.